Pengaruh Model Problem Based Learning Berbantuan E-Modul Flipbook terhadap Hasil Belajar Peserta Didik Materi Getaran Harmonik - Samsul Afandi; Sutrio; Aris Doyan (Mataram University, 2026)
This study aimed to determine the effect of the Problem-Based Learning (PBL) model assisted by a flipbook e-module on students' learning outcomes in harmonic oscillation. The study employed a quasi-experimental method using a non-equivalent control group design. The population consisted of all eleventh-grade students at SMAN 1 Praya Barat. Purposive sampling was used to select class XI A1 as the experimental group, which received the Problem-Based Learning model assisted by a flipbook e-module, and class XI A2 as the control group, which received conventional instruction. Data were collected using a cognitive learning achievement test, an affective observation sheet, and a psychomotor assessment sheet, all of which had been validated and tested for reliability. Data were analyzed using an independent samples t-test at a 5% significance level after fulfilling the assumptions of normality and homogeneity. The results showed that the mean cognitive pretest scores of the experimental and control groups were 62.31 and 61.73, respectively, while the mean posttest scores were 75.58 and 69.04. The experimental group also achieved higher mean scores in the affective domain (70.77 vs. 67.62) and psychomotor domain (80.46 vs. 69.42) than the control group. Hypothesis testing revealed significance values of 0.007 for the cognitive domain, 0.044 for the affective domain, and 0.000 for the psychomotor domain. These findings indicate that the implementation of the Problem-Based Learning model assisted by a flipbook e-module has a significant positive effect on improving students' learning outcomes in harmonic oscillation.